Kem Bumi Jati 3D walkthrough application - Muhammad Afiful Munir, Mutalib (2014)
This main aim of this project is to develop a walkthrough application using 3D Walkthrough technology for Kem Bumi Jati. 3D walkthrough sometimes being called 3D Environment which means the technology that allows users to interact and immerse with a computer-simulated environment be it a real one or imagined one. The purpose of this project is to develop "Kem Bumi Jati 3D Walkthrough Application" where it will display and show the camping side environment and buildings in 3D environment and this project will cover for the whole Kem Bumi Jati which containing "Dewan Cemerlang", "Dewan Makan" and etc. This proposal was propose when realizing this technology is still lack in the tourism and business area in Malaysia. This project has given benefits to the targeted audience who are potential visitors, existing clients and workers where they can interact to the 3D model nearer and feel the technology itself. This Windows based application will be develop using Unity3D to get the environment and Maya software to develop and create the building's model. As a conclusion, this report was prepared so to make it clear about the workflow and process development through this project.